Alternative splicing of leptin receptor overlapping transcript in osteosarcoma. Issue 16 (October 2020) - Rothzerg, Emel; Ho, Xuan D; Xu, Jiake; Wood, David; Märtson, Aare; Maasalu, Katre; Kõks, Sulev
Alternative splicing of RNA is an essential mechanism that increases proteomic diversity in eukaryotic cells. Aberrant alternative splicing is often associated with various human diseases, including cancer. We conducted whole-transcriptome analysis of 18 osteosarcoma bone samples (paired normal—tumor biopsies). Using RNA-seq, we identified statistically significant (FDR <0.05) 26 differentially expressed transcript variants of leptin receptor overlapping transcript ( LEPROT ) gene. Some of the transcripts were overexpressed in normal cells, whereas others were overexpressed in tumor cells. The function of LEPROT is not completely understood. Herein, we highlight a possible association between OS and aberrant alternative splicing events and its interaction with the expression of LEPROT . We also discuss the role of LEPROT in regulating growth hormone and its receptor, and the relationship with initiation and progression of OS. This research study may help to understand the association of alternative splicing mechanism in OS and in tumorigenesis more generally. Further, LEPROT gene can also be considered as a potential biomarker of osteosarcoma. Impact statement: Osteosarcoma (OS, also known as osteogenic sarcoma) is the most common primary malignancy of bone in children and adolescents. The molecular mechanisms of OS are extremely complicated and its molecular mediators remain to be elucidated. We sequenced total RNA from 18 OS bone samples (paired normal—tumor biopsies). We found statistically significant (FDR <0.05) 26 differentially expressed transcript variants of LEPROT gene with different expressions in normal and tumor samples. These findings contribute to the understanding of molecular mechanisms of OS development and provide encouragement to pursue further research.